2003
DOI: 10.1021/jp030971b
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization and Dissociation of CHNS:  Quantum Mechanical Study

Abstract: An extensive quantum mechanical study of the potential energy surface for the isomerization and dissociation reactions of CHNS is reported. The calculations were performed using density functional theory and correlated ab initio methods and employing large aug-cc-pVTZ basis set. Nine CHNS isomers and eleven transition states linking them have been found on the singlet PES. Dissociation energies of the singlet most stable open chain CHNS isomers have been evaluated. On the triplet PES, eight mostly highly energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 26 publications
3
44
0
Order By: Relevance
“…The close harmonicity of lines in the K a = 0 ladder and the absence of fine structure confirms that the carrier is a closed-shell molecule. The measured rotational constants B and C agree to better than 0.2% with those predicted from two theoretical calculations (Wierzejewska & Moc 2003;Durig et al 2006), providing strong evidence that HSCN is the carrier of the observed lines. Hfs in the lower rotational transitions and quadrupole coupling constants within 15% of those predicted show that the molecule contains nitrogen, as illustrated in the sample spectrum of the 2 0,2 − 1 0,1 transition (Figure 3).…”
Section: Centimeter-wave Spectrumsupporting
confidence: 74%
See 2 more Smart Citations
“…The close harmonicity of lines in the K a = 0 ladder and the absence of fine structure confirms that the carrier is a closed-shell molecule. The measured rotational constants B and C agree to better than 0.2% with those predicted from two theoretical calculations (Wierzejewska & Moc 2003;Durig et al 2006), providing strong evidence that HSCN is the carrier of the observed lines. Hfs in the lower rotational transitions and quadrupole coupling constants within 15% of those predicted show that the molecule contains nitrogen, as illustrated in the sample spectrum of the 2 0,2 − 1 0,1 transition (Figure 3).…”
Section: Centimeter-wave Spectrumsupporting
confidence: 74%
“…Our laboratory search for HSCN was guided by rotational constants derived from published quantum calculations (Wierzejewska & Moc 2003;Durig et al 2006), and nitrogen-14 quadrupole coupling constants calculated by us. A search near 11.5 GHz, the predicted frequency of the fundamental a-type rotational transition (J K a ,K c = 1 0,1 → 0 0,0 ), was undertaken first.…”
Section: Centimeter-wave Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the interstellar abundance ratio HNCS/ NCSH, found to be 2-7 in Sgr B2 (Adande et al 2010;Halfen et al 2009) and close to unity in TMC-1 (Adande et al 2010), is completely different from the value of approximately 200 observed for HNCO/HOCN (Brünken et al 2009a;Marcelino et al 2010;Adande et al 2010). HSCN is, however, as much as 26 kJ mol −1 less stable than HNCS (Wierzejewska & Moc 2003). Adande et al (2010) proposed that these findings be rationalized in terms of both HNCS and NCSH arising from a common precursor species HNCSH + -which would resemble the commonly accepted scheme of HCN/CNH synthesis from HCNH + (Ziurys & Turner 1986).…”
Section: Introductionmentioning
confidence: 72%
“…HNCS and HSCN were predicted as the lowest energy structures among the molecules sharing the same stoichiometry, with HSCN being 26 kJ/mol less stable than HNCS (Wierzejewska & Moc 2003). The importance of HSCN would therefore be negligible if thermodynamic equilibrium between the two species existed.…”
Section: Introductionmentioning
confidence: 98%